Is Short beautiful? Food supply chains and the promotion of sustainability through the lens of social innovation - Sousa, C.; Ferreiro, Maria de Fátima (5th Euro Mediterranean Conference for Environmental Integration, 2023)
This paper examines the role of social innovation for sustainable food transition, focusing on Short Food Supply Chains (SFSCs). SFSCs can offer alternative ways of producing and consuming food that are more aligned with the principles of sustainable development and may offer mutual benefits to both farmers and consumers. However, the empirical evidence on SFSCs is still scarce and frag-mented, and the theoretical and methodological frameworks for analyzing them are underdeveloped. In this paper SFSCs are seen as a social innovation and the main research question that guides our inquiry is: How can this social innovation enable a sustainable food transition that meets the needs of people and the planet? The results show that SFSCs can generate positive outcomes for producers, con-sumers, and the environment, promoting sustainability goals in their three dimen-sions (economic, social, environmental). However, they also highlight the chal-lenges and trade-offs involved in scaling up and sustaining SFSCs